Imanensi dan Transendensi Petara Raja Juwata Sebagai Wujud Tertinggi Orang Dayak Desa Kalimantan Barat - Kwirinus, Dismas (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2022)
The focus of this study is to explain the immanence and transcendence of Petara Raja Juwata as the highest form of the Dayak Desa of West Kalimantan. The idea of the Dayak people of West Kalimantan knowing the Supreme Being arises from the human imagination that connects the events experienced with a force that rules the universe. The important thing about this Supreme Being is that this nature does not exist from itself but that there is something that creates it. The Village Dayak people call this Supreme Being as Petara Raja Juwata. Petara Raja Juwata is a center and a “religious” experience. Reli[1] gious life is a theophanic experience that affects all human life. Petara Raja Juwata is real, full of power, the source of all life and energy. Petara Raja Juwata is truly transcendent, a reality that does not belong to the world even though it is manifested in and through the world. Petara Raja Juwata is also essentially ambivalent, enchanting and frightening at the same time, the cause of life and death. Petara Raja Juwata is also approachable, He is immanent. He is close, lives and is involved in the daily life of the Desa Dayak people. This paper aims to describe, analyze the concept of Petara Raja Juwata as transcendent and at the same time immanent. The author uses a phenomeno[1] logical analysis methodology in the perspective of Valentinus Saeng in his presentation of the Mualang Dayak religion in myth. The type of research used is a qualitative research method. The findings in this study are that the Desa Dayak people in West Kalimantan are aware that Petara Raja Juwata as the Supreme Being of the Desa Dayak people is both immanent and transcendent.